The Effectiveness of Environmental Policy in Addressing Climate Change - Dao, Sái Quỳnh (Journal of Public Representative and Society Provision, 2023)
The purpose of this research is to analyse the efficiency of environmental policies in mitigating climate change and the part played by stakeholders, political stability, policy research and policy fairness. In this research, quantitative to complement quantitative method has used to establish that where policies are made through public consultation, the policies will be effective in achieving its set objectives. It also focuses on the aspect of political stability and leadership on the ability to enhance policies ‘implementation and enforcement. In addition, data driven policies aligned with current and contextualized scientific knowledge to tackle environmental issues were determined to be more efficient. Last of all, the research also proves that ANT’s policies are more sustainable in the long run and those that strive at enhancing social equity and environmental justice are vital for achieving other environmental objectives. Based on these findings, it can be concluded that the combination of these factors in environmental policymaking is essential to fight climate change and support sustainable development.